Person-centred rhetoric in chronic care: a review of health policies. Issue 2 (5th February 2020) - Sobolewska, Agnieszka; Byrne, Amy-Louise; Harvey, Clare Lynette; Willis, Eileen; Baldwin, Adele; McLellan, Sandy; Heard, David
Abstract : Purpose: The purpose of the paper is to explore how the national, state and organisational health policies in Australia support the implementation of person-centred care in managing chronic care conditions. Design/methodology/approach: A qualitative content analysis was performed regarding the national, state and organisational Queensland Health policies using Elo and Kyngas' (2008) framework. Findings: Although the person-centred care as an approach is well articulated in health policies, there is still no definitive measure or approach to embedding it into operational services. Complex funding structures and competing priorities of the governments and the health organisations carry the risk that person-centred care as an approach gets lost in translation. Three themes emerged: the patient versus the government; health care delivery versus the political agenda; and health care organisational processes versus the patient. Research limitations/implications: Given that person-centred care is the recommended approach for responding to chronic health conditions, further empirical research is required to evaluate how programs designed to deliver person-centred care achieve that objective in practice. Practical implications: This research highlights the complex environment in which the person-centred approach is implemented. Short-term programmes created specifically to focus on person-centred care require the right organisational infrastructure, support and direction. This review demonstrates the need for alignment of policies related to chronic disease management at the broader organisational level. Originality/value: Given the introduction of the nurse navigator program to take up a person-centred care approach, the review of the recent policies was undertaken to understand how they support this initiative.